Attention and behavioral control skills in Iranian school children - Kiani, Behnaz; Hadianfard, Habib; Mitchell, John T. (Attention deficit and hyperactivity disorders, 2019)
This study assessed quality of life, emotional and behavioral problems, prosocial behavior, and functional impairment in a sample of Iranian children based on their attention and behavioral control skills. The sample consisted of 280 male and female children aged between 6 and 12 years old who were divided into strong, moderate, and weak groups based on parental ratings of attention and behavioral control skills on the strengths and weaknesses of ADHD symptom and normal behavior rating scale (SWAN). In addition, parents completed the pediatric quality of life inventory version 4.0 generic core scales (PedsQL 4.0), the strengths and difficulties questionnaire, and the Weiss functional impairment rating scale-parent report (WFIRS-P). The strong group generally showed better quality of life than the weak group. The strong group was better than the moderate group, and the moderate group was better than the weak group on school functioning. The weak group had more conduct problems and hyperactivity/inattention and less prosocial behavior than the moderate group and the strong group. The moderate group had more hyperactivity/inattention than the strong group. The weak group showed more impairment than the moderate group and the strong group on all subscales and the total scale of the WFIRS-P. The quality of life, behavioral problems, prosocial behavior, and functional impairment can be different in children based on their attention and behavioral control skills.